α-Lipoic acid can not prevent effet on cell viability, collagen synthesis inhibition, collagen degradation induction in ultraviolet A irradiated human fibroblast cell - Putu Dyah Ayu Saraswati Soedirman Sastrodiprodjo Yohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Ultraviolet A (UVA) irradiation on human skin can generate free radical and stimulate matrix metalloproteinaseproduction resulting in collagen degradation and transforming growth factor beta (TGF-β) inhibition. It causes synthesiscollagen inhibition and induces cell death. α-Lipoic acid (ALA) is an universal antioxidant and a powerful scavengerof free radicals. In this study we investigated the effect of ALA on viability, collagen synthesis and degradation inUVA irradiated human fibroblasts. Normal human skin fibroblasts cell culture were irradiated with UVA for threetimes with each dose of 3000 mJ/cm2 UVA. α-Lipoic acid in various concentration was added to the culturefollowing UVA irradiation and incubated for 48 hours. The cell viability was determined by MTT-assay while collagensynthesis and degradation were determined by Sirius red binding assay. The difference of cell viability and collagensynthesis and degradation between fibroblasts cell after and without UVA irradiation were analyzed using paired-ttest with 95% confidence interval (p<0.05). The results showed that UVA irradiation decreased cell viability,inhibited collagen synthesis and induced collagen degradation in fibroblasts cell. However, ALA was not sufficient toincrease viability, to increase collagen synthesis and to inhibit collagen degradation in fibroblasts cell due to UVAirradiation. In conclusion, ALA can not prevent UVA irradiation effect on human skin fibroblasts cell.Key words: UVA – irradiation - human skin fibroblasts – antioxidants – α-lipoic acid